BENCHMARK ANALYSIS OF LIVESTOCK FARMERS OF DODDABALLAPURA TALUK, KARNATAKA - PAVAN BELAKARI and G.K. CHANDRA SHEKAR, E. MUTTURAJ YADAV, M. KIRAN, K. JAGADEESWARY, K. SATYANARAYANA (The Journal of Research, PJTSAU, 2017)
The livestock sector alone contributes nearly 25.6 per cent of value of Output at current prices of total value of output in Agriculture, Fishing & Forestry sector. The overall contribution of Livestock Sector in total GDP is nearly 4.11 per cent at current prices during 2012-13 (19th Livestock census, 2012). The number of milch animals in-milk and dry among cows and buffaloes has increased from 111.09 million to 118.59 million and the animals in milk in cows and buffaloes has increased from 77.04 million to 80.52 million. India possesses the highest strength of buffaloes, third highest number of sheep, holds second highest position in goat population, fifth highest number of chicken (Basic Animal Husbandry Statistics, 2003). In spite of the rich animal wealth, the productivity in the livestock sector is less than its optimum.